2013
DOI: 10.1521/pdps.2013.41.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Transference-Focused Psychotherapy in the General Psychiatry Residency: A Useful and Applicable Model for Residents in Acute Clinical Settings

Abstract: Transference-focused psychotherapy (TFP) is a manualized, psychodynamic treatment for severe personality disorders. Training in TFP during residency can provide a readily applicable model for understanding and treating personality pathology in a variety of settings, even for residents who do not obtain additional training in psychodynamic treatments or go on to practice psychotherapy. Although TFP was developed as a long-term outpatient treatment, the authors have found the diagnostic and theoretical framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 9 publications
0
33
1
Order By: Relevance
“…However, contrary to the expectations of the residents and the training director, the elective in TFP strengthened understanding of core components of basic psychodynamic psychotherapy with all patients, not just those with severe personality disorders. Zerbo, Cohen, Bielska, and Caligor (2013) have observed that training in TFP helps residents develop "knowledge, attitudes, and skills" that can be deployed to help patients with personality disorders in many settings outside of the outpatient psychotherapy clinic, including many acute settings such as inpatient medical and psychiatric units. In this article, we will argue that TFP training helps residents understand basic psychodynamic psychotherapy with all patients, not just those for whom TFP was designed.…”
mentioning
confidence: 99%
“…However, contrary to the expectations of the residents and the training director, the elective in TFP strengthened understanding of core components of basic psychodynamic psychotherapy with all patients, not just those with severe personality disorders. Zerbo, Cohen, Bielska, and Caligor (2013) have observed that training in TFP helps residents develop "knowledge, attitudes, and skills" that can be deployed to help patients with personality disorders in many settings outside of the outpatient psychotherapy clinic, including many acute settings such as inpatient medical and psychiatric units. In this article, we will argue that TFP training helps residents understand basic psychodynamic psychotherapy with all patients, not just those for whom TFP was designed.…”
mentioning
confidence: 99%
“…Zerbo, Cohen, et al describe a model for consultation-liaison psychiatrists to utilize in the general hospital setting when encountering patients with personality disorders [42]. Though intended for mental health specialists, much can be learned that can be utilized by the nonmental health clinician.…”
Section: Patient and Medical Clinician As Subjective Beingsmentioning
confidence: 99%
“…Individuals with personality problems present particularly difficult challenges for medical staff in that they may be dissatisfied with their care or caregivers and can be generally difficult to get along with; they prove particularly vexing, however, in their capacity to arouse uncomfortable feelings in those around them. Based on Transference-Focused Psychotherapy (TFP), an evidence-based, manualized psychodynamic treatment for people with personality disorders [43], Zerbo et al [42] model makes use of those very unpleasant feelings that these patients induce in the clinician. This model understands these counter-transferential experiences as reflections of the feelings the patient disowns because they are too painful for him or her to tolerate.…”
Section: Patient and Medical Clinician As Subjective Beingsmentioning
confidence: 99%
“…TFP has also been introduced in the treatment of personality disorders in a group treatment format (Kernberg, 2012). In addition, TFP has been introduced as a teaching tool in psychiatry residency training for use in acute settings such as inpatient general psychiatry, forensic psychiatry, and substance use disorder units (Zerbo, Cohen, Bielska, & Caligor, 2013).…”
mentioning
confidence: 99%
“…While the relationship between a prescribing clinician and patient can be an established and predictable one, prescribers also at times find themselves evaluating and treating patients whom they hardly know. Zerbo et al (2013) described the usefulness of TFP training for psychiatry residents in mastery of an organizing theoretical framework for both diagnosis and clinical process to be used in acute care settings with patients whom they may not know well, if at all. They note that TFP training may be of use to residents who do not pursue additional psychotherapy training after completing residency and suggest that TFP principles are helpful in settings like the psychiatric emergency room, inpatient psychiatric units, and medical units, where trainees often are required to manage difficult situations with patients with personality disorders.…”
mentioning
confidence: 99%